ANALISIS PENGARUH KOMPENSASI DAN PENGEMBANGAN KARIER TERHADAP KEPUASAN KERJA DENGAN MEDIASI MOTIVASI KERJA (Studi pada PNS di Sekretariat Daerah Kabupaten Pekalongan) - Dwi Nugroho, Agus; Kunartinah Kunartinah (Jurnal Bisnis dan Ekonomi, 2012)
This research aims to analyze the impact of Compensation and Career Development toward Job Satisfication with JobMotivation as mediation. Questioner with 1-7 Likert scale is used as instrument to obtain the data. To test validity, thisresearch uses factor analysis and to test the reliability usus standard of apha 0,6. Linear regression is used as analysismethod. To test the influence of variable partially uses significancy test as 5 percent, while to test the mediation impact usesPath Analysis. Object of this researchis the civil servants at Regency Secretary of Pekalongan Regency with 255 peoples aspopulation and 108 peoples as responden. Based on the multiple linear regression analysis model I, compensation and careerdevelopment variable have positive effect and significant to job motivation variable. From determination Adjusted R Square =0,474, means that 47,4 percent change of in job motivation variable is explained by compensation and career developmentvariable. From the multiple linear regression analysis model II, compensation, career development and job motivationvariable have positive effect and significant to job satisfaction variable. To be found that highest contribution for jobsatisfaction variable is from compensationt variable 0,524 and Adjusted R Square = 0,727, means that 72,7 percent changeof job satisfaction variable explained by compensation, career development and job motivation variable. The result of thisresearch can be effort to increase civil servants at Regency Secretary of Pekalongan Regency’s job satisfication by giving theright of compensation and career development, with increasing job motivation, it is one of way to effort human resourcesretention in an organization.Key words: compensation, career development, job motivation and job satisfication